(3TQM MeGSI CHj JeGes - (3CHi Ydj CMeO Hf eMeO Hf GdMSf GdeQRhbis; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s ((3eMeO Hf GdOQi GdMfai s)
(3ChdgG (B:s
(3hHYO aEfc LGRjJfi CWGd Gddg HbGAc deG QCjJg CbUQ eeG CSJaVdg Edi JeGe MHjH GHf ChS GdWGFi GdeYQha HcJGH GdMeGSg s
(3BNQgG (B:s
(3jbGd GaJVVJ GdcQT EPG GSJNQLJ Pdc GdeGA ajg hGdeYfi hdG fGd GdaX ai HWf Pdc GdUjO jYaQG , Ci jSbW ai GdYaQ Je GdLRA GdChd ,(B[(3hjdjg(B] (3GdLRA GdKGfi ef GdMeGSI ddeQRhbj s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B100 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B692s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs